Otępienia jako choroby cywilizacyjne i społeczne XXI wieku = Dementia as a civilization and social diseases of the 21st century - Oliwia Beck; Mateusz Łakomski; Kornelia Kędziora-Kornatowska; Agnieszka Radzimińska; Magdalena Weber-Rajek; Walery Zukow (Kazimierz Wielki University, 2016)
Beck Oliwia, Łakomski Mateusz, Kędziora-Kornatowska Kornelia, Radzimińska Agnieszka, Weber-Rajek Magdalena, Żukow Walery. Otępienia jako choroby cywilizacyjne i społeczne XXI wieku = Dementia as a civilization and social diseases of the 21st century. Journal of Education, Health and Sport. 2016;6(6):677-694. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.101640 http://ojs.ukw.edu.pl/index.php/johs/article/view/3865       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016.     Otępienia jako choroby cywilizacyjne i społeczne XXI wieku Dementia as a civilization and social diseases of the 21st century   Oliwia Beck1,2, Mateusz Łakomski2, Kornelia Kędziora-Kornatowska2, Agnieszka Radzimińska3, Magdalena-Weber-Rajek3, Walery Żukow4   1Katedra Zdrowia Publicznego, Wydział Nauk o Zdrowiu, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy UMK w Toruniu 2Katedra i Klinika Geriatrii, Wydział Nauk o Zdrowiu, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy UMK w Toruniu   3Katerda Fizjoterapii, Zakład Podstaw Fizjoterapii, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy UMK w Toruniu 4Uniwersytet Kazimierza Wielskiego, Bydgoszcz     Streszczenie Starzenie się społeczeństw wpłynęło na zwiększenie zainteresowania zaburzeniami procesów poznawczych, dla których najważniejszym czynnikiem ryzyka jest wiek. Notowany wzrost liczby zachorowań związany jest wiec przede wszystkim z wydłużeniem się średniej długości życia współczesnych społeczeństw cywilizacyjnych. Terminem, którego używa się na określenie wielu różnych chorób mózgu, których wspólną cechą jest utrata funkcji intelektualnych i poznawczych, jest otępienie. Praca przedstawia kluczowe informacje dotyczące zaburzeń neurodegeneracyjnych, w tym najczęściej występującej choroby Alzheimera, stanowiącej wyzwanie dla zdrowia publicznego. słowa kluczowe: starzenie się, otępienie, choroba Alzheimera Abstract Recent population ageing has contributed to the growth of interest in cognitive impairments. The most important risk factor for cognitive impairments is age. Current and predicted socio-demographic trends have made these issues important for an ever - increasing number of people and pose a major public health concern. The term that describes multiple neurodegenerative disorders of the brain, which common feature is the loss of intellectual and cognitive functions, is dementia. The paper describes the key data on neurodegenerative disorders, including Alzheimer's disease, being the leading cause of dementia worldwide.   key words: ageing, dementia, Alzheimer's Disease